The Effect of Health Education on The Prevention of Leptospirosis Events in The Dormitory Environment - Noradina, Noradina (Universitas Aisyah Pringsewu, 2020)
Leptospirosis is a zoonotic disease caused by the bacteria Leptospira sp. Leptospirosis is often found in tropical and developing countries, including Indonesia. Leptospira bacteria are the cause of leptospirosis that can attack animals and humans. Infection in humans is an incidental event because the main reservoir or spreader of Leptospira is rats. The urine of mice infected with Leptospira mixed or contaminated with water used for bathing can enter the human body through injured skin and mucous membranes. Prevention efforts are one way to reduce the incidence of leptospirosis, one of which is to cultivate good attitudes and knowledge about leptospirosis. This type of research is quantitative using a one-group pre-post test design. The sample in this study was Imelda Medan university students with a total of 30 respondents using accidental sampling. Data analysis using the Wilcoxon test. The results showed that there was a significant difference (p less than 0.05) in the average knowledge of respondents before and after the intervention, meaning that there was an increase in respondents' knowledge of leptospirosis prevention.